2016
DOI: 10.1016/j.ijporl.2016.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Do race/ethnicity or socioeconomic status affect why we place ear tubes in children?

Abstract: Introduction Despite recent concerns about potential overuse of tympanostomy tube (TT) placement to treat otitis media in children, utilization of this common procedure in the U.S. has been shown to be relatively less common among minority children. It is not known if the indications for TT differ by child race/ethnicity and/or socioeconomic status (SES). Our objective is to analyze the association of patient- and neighborhood-level demographics and SES with clinical indications for TT. Methods We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 47 publications
1
31
2
Order By: Relevance
“…Whereas we found no disparity between demographic variables in the provision of MTs, a recently published report from Nieman et al indicated a differential of MT indication based on socioeconomic status. The authors demonstrated that children from high poverty areas were more likely than children from low poverty areas to receive MTs for OME, as opposed to recurrent acute otitis media.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Whereas we found no disparity between demographic variables in the provision of MTs, a recently published report from Nieman et al indicated a differential of MT indication based on socioeconomic status. The authors demonstrated that children from high poverty areas were more likely than children from low poverty areas to receive MTs for OME, as opposed to recurrent acute otitis media.…”
Section: Discussioncontrasting
confidence: 98%
“…These findings are similar to the findings from Shay et al, which showed that black and Hispanic children were less likely to be identified or diagnosed with frequent ear infections, hay fever, streptococcal pharyngitis, or sinusitis as compared to white children. 3 Whereas we found no disparity between demographic variables in the provision of MTs, a recently published report from Nieman et al 20 indicated a differential of MT indication based on socioeconomic status. The authors demonstrated that children from high poverty areas were more likely than children from low poverty areas to receive MTs for OME, as opposed to recurrent acute otitis media.…”
Section: Discussioncontrasting
confidence: 53%
“…Children of lower SES experienced a wide range of disparities compared to higher SES peers, from higher rates of hearing loss to lower utilization of hearing rehabilitation to increased risk of post‐tonsillectomy complications (as summarized in Table ) . These are often independent of race and even insurance status . Myriad factors including income, education, and physical environment are associated with low SES.…”
Section: Discussionmentioning
confidence: 99%
“…Some emerging evidence suggests that, among children receiving PET placement, white children may be more likely to receive PET placement for RAOM, while black children were more likely to receive PET placement for COME. 30 However, until 2013, PET placement was not suggested in guidelines for the treatment of AOM prior to 2013. 4, 31 Most children who received PET placement in this study would have had placement prior to 2013.…”
Section: Discussionmentioning
confidence: 99%